ON INTUITIONISTIC b - OPEN SETS - PRABHU, A.; VADIVEL, A.; SATHIYARAJ, J. (International Journal of Mathematical Archive, 2018)
In this paper, we introduce a new types of sets called intuitionistic -open sets in intuitionistic topological space. Also intuitionistic -interior and intuitionistic -closure of an intuitionistic sets are defined and their properties are investigated with other existing forms of intuitionistic open sets.